Spatiotemporal Modeling of Acid Rain Chemistry in Tropical Java Using Mixed-Effects Models: Deposition Patterns and Threshold Exceedance - Ahmad Romli, Rita Hidayati; Mochamad Aryono Adhi; Adi Mulsandi (Jurnal Meteorologi dan Geofisika, 2025)
Acid deposition in tropical regions remains under-characterized despite rapid urbanization and increasing atmospheric emissions. This study examines the spatiotemporal variability of rainwater acidity across Java Island, Indonesia, based on five years (2019–2023) of event-based observations from thirteen monitoring stations. Weekly measurements of pH, SO₄²⁻, NO₃⁻, NH₄⁺, Cl⁻, and rainfall volume were analyzed using spatial mapping, seasonal stratification, and linear mixed-effects modeling. The results show that 47% of rain events exhibited pH values below 5.6, while sulfate and nitrate concentrations exceeded critical ecological thresholds in up to 34% of cases, particularly during monsoon transition periods. Although ammonium buffering was observed, it was often insufficient in urban areas. Rainfall volume was significantly associated with ion concentrations; however, episodic acidic deposition remained substantial even during periods of high precipitation. These findings highlight the dual role of tropical rainfall as both a cleansing mechanism and a vector for atmospheric pollutants and provide a scientific basis for incorporating acid deposition into Indonesia’s environmental monitoring and management programs.